The right stuff - Wolfe, Tom. (London : Pan books, 1991)
Men first flew into space in 1961, but until The Right Stuff was first published in 1979 few people had a sense of the most engrossing side of that adventure: namely, the perceptions and goals of the astronauts themselves, aloft and during certain remarkable odysseys on earth. It is this, the inner world of the early astronauts, John Glenn, Alan Shepard, Gus Grissom, and their confreres, that Tom Wolfe describes with his extraordinary powers of empathy. He shows us the bidden olympus to which all ambitious combat and test pilots aspired, the top of the pyramid of the right stuff. And we learn the nature of the ineffable pilot's grace without which all else meant nothing. We see the men whose achievements dominated the flying fraternity in the late 1950's as the space age began, men like Chuck Yeager and Joe Walker, pilots of the first rocket planes, most notably the X-1 and the X-15. The selection of the Mercury astronauts in 1959 shook up the fraternity as thoroughly as had Yeager's breaking of the sound barrier twelve years before. Public excitement and concern over the space race with the Soviets immediately elevated the seven astronauts to the uneasy eminence of heroes, long before their first flight. We see the seven men, in the very moment of their idolization by the outside world, struggling to gain the respect of their peers within the flying fraternity, even to the point of altering NASA's original conception of the astronaut's role in keeping with the unspoken prerequisites of the right stuff. - Author web site.
Keywords: Astronautics -- United States; Astronauts -- United States